Third wave of COVID-19 in Madrid, Spain - Vicente Soriano; Carmen de Mendoza; Felix Gómez-Gallego; Octavio Corral; Pablo Barreiro (International Journal of Infectious Diseases, 2021)
A third wave of COVID-19 occurred after Christmas 2020 in Madrid, one of the European pandemic epicenters. We noticed 6 major differential features to previous waves. First, household contacts were a large proportion of cases. Second, access to rapid antigen tests allowed prompt diagnosis and isolation. Third, clinically severe cases and mortality rates were lower. Fourth, the more transmissible B.1.1.7 strain was increasingly found. Fifth, vaccination benefits were seen in healthcare workers and nursing homes. Lastly, reinfections were more common. By Easter 2021, approximately 25% of the population in Madrid had been infected with SARS-CoV-2. Therefore, massive and accelerated vaccination campaigns are warranted to prevent new COVID-19 waves.